Generalized Reed-Solomon codes over number fields and exact gradient coding - Irwansyah; Intan Muchtadi-Alamsyah; Fajar Yuliawan; Muhammad Irfan Hidayat (AIMS Mathematics, 2024)
This paper describes generalized Reed-Solomon (GRS) codes over number fields that are invariant under certain permutations. We call these codes generalized quasi-cyclic (GQC) GRS codes. Moreover, we describe an application of GQC GRS codes over number fields to exact gradient coding.